Zwitterionic materials for photonic applications - Kuczynski, Andrzej. Piotr. (Cranfield University, 1992)
A series of zwitterionic materials of general formula R-D*-CH=C(CN)- CÖH4-C(CN)2', where D* is a pyridirium or quinolinium acceptor and R is a hydrophobic alkyl chain or an aryl group, were deposited using the Langmuir- Blodgett (LB) technique and their photochromic and nonlinear optical properties characterised. The materials are highly solvatochromic, exhibiting a broad photochromic charge transfer band in the visible region which bleaches when irradiated. LB films of the zwitterions, Z-ß-(1-hexadecyl-4-pyridinium)-a-cyano-4- styryldicyanomethanide (CMH33-P3CNQ) and the quinolinium analogue, Z-ß-(1- hexadecyl-4-quinolinium)-a-cyano-4-styryldicyanomethanide (CIÖH33-Q3CNQ), are non-centrosymmetric (Z-type). They exhibit sharp charge transfer bands at 495 n ana ses n respecivey with haf widths ai half maximum of 27 and zz mi. Unusually, mixed LB films of CIGH33-P3CNQ and C161-133-Q3CNQ exhibit a single sharp charge transfer band whose position is dependent upon the mole fraction and is finely tunable in the range 495 to 565 nm. These films are photobleached when irradiated at wavelengths which overlap the absorption bands, and may find potential applications a components of a multifrequency optical memory. Also, the unique peak wavelength tuning of the heteromolecular films enabled the effect of the position of the absorption band on second harmonic generation to be investigated for the first time. The zwitterionic materials have exciting norlinear optical properties and the strongest second harmonic intensity from any LB film has been obtained. LB films of the quinolinium zwitterion (CMH33-Q3CNQ) are non-centrosymmetric and the second harmonic intensity increases quadratically with the number of layers deposited to thicknesses of ca. 1 m. It is one of only five known materials to show such behaviour and the second-order susceptibility (xa) = 180 pm V* at 1064 nm) is the highest value obtained for a multilayer structure.